The Economic Sanctions Channel for The Curse of The Petro-State of Iran: Evidence from the Synthetic Control Method - Ertimi, Basem Ertimi; Cahyadin, Malik; Sarmidi, Tamat Tamat (Jurnal Ekonomi Kuantitatif Terapan; Vol 17 No 2 (2024): Vol. 17, No. 2, Agustus 2024 (pp.156-369), 2024)
This study estimates the impact of economic sanctions on oil exports and economic growth in the case study of Iran. By creating a synthetic control group method that reproduces the oil exports and economic growth before economic sanctions are imposed in the case of Iran, we compare the oil exports as well as the economic growth of the Synthetic and the actual for each period. Using the synthetic control method, we fill a major gap in the sanctioned literature in the petrostate economies case study. Our study finds that both oil exports and the economic growth of Iran would have been lower had it not been exposed to economic sanctions. This research is embedded in the comparative and international landscape linked to the relations of international influences with the domestic economy. The findings explain that economic sanctions are a leading factor in the variations in oil exports and economic growth, which can be reflected in the oil curse. We claim that our empirical investigation can contribute to policy formulation in the domestic and foreign arena by sanctioned countries. Overall, the findings confirm that the imposition of sanctions on a petrostate economy like (Iran) can be operated as another channel of the resource curse from international and foreign policy perspectives.